Developing Measures of Placement Quality in Allied Health, Dentistry, Medicine, and Pharmacy - McAllister, Lindy; Nagarajan, Srivalli; Scott, Linda; Smith, Lorraine; Thomson, Kate (International Journal of Practice-based Learning in Health and Social Care, 2018)
As placement numbers expand, there is a concern that the quality of student experience and learning may diminish. Furthermore, there is a paucity of evidence for evaluation and quality improvement in clinical health placements and there have been few studies undertaken to assess quality. Valid and reliable measures of placement quality are needed to provide an evidence-base to guide decisions about the most efficient and effective placement models in health. A two-phase mixed methods design, using a modified Delphi process, focus groups, and surveys, developed and tested items to measure placement quality. Thematic analysis, descriptive statistics, and exploratory factor analysis (EFA) were used to analyse the data. Twenty-three participants took part in the Phase 1 stakeholder focus groups, and 150 useable surveys were returned by 161 who took part in Phase 2 to test validity and reliability of the student survey items. Results show broad agreement on the features of a quality clinical placement across allied health dentistry, medicine, and pharmacy professions. The student survey was found to be a valid and reliable measure of placement quality, with the EFA showing one component accounting for 58.5% of the variance in the survey data. The findings offer a framework and approach that others can adopt to measure placement quality in their setting. The measures may be adaptable to contexts outside health.